Evidence of reversible oxygen participation in anomalously high capacity Li- and Mn-rich cathodes for Li-ion batteries. (March 2016) - Muhammad, Shoaib; Kim, Hyunchul; Kim, Yunok; Kim, Donghwi; Song, Jay Hyok; Yoon, Jaegu; Park, Jin-Hwan; Ahn, Sung-Jin; Kang, Sun-Ho; Thackeray, Michael M.; Yoon, Won-Sub
Abstract: The reaction mechanism of a high capacity lithium- and manganese-rich metal oxide, 0.4Li2 MnO3 –0.6LiMn0.5 Ni0.5 O2, has been investigated at the atomic level. High-resolution synchrotron X-ray powder diffraction (HRPD) and X-ray absorption spectroscopy (XAS) were used, respectively, to evaluate the electrochemical charge and discharge reactions in terms of local and bulk structural changes, and variations in the oxidation states of the transition metal ions. Ni K-edge XAS data indicate the participation of nickel in reversible redox reactions, whereas Mn K-edge absorption spectra show that the manganese ions do not participate in the electrochemical reactions. Rietveld refinements of the oxygen occupancy during charge and discharge provide evidence of reversible oxygen release and re-accommodation by the host structure; this unique oxygen participation is likely the main reason for the anomalously high capacity of these electrodes. The HRPD data also show that during the early cycles, characteristic peaks of the Li2 MnO3 component disappear when charged to 4.7 V, but reappear on discharge to 2.5 V, consistent with a reversible lithium and oxygen extraction process. The results provide new insights into the charge compensation mechanisms that occur when high capacity, lithium- and manganese-rich electrode materials are electrochemically cycled – a topic that is currently being hotly debated in the literature. Graphical abstract: Highlights: Anomalous high capacity of Li- and Mn-rich electrodes has been probed by HRPD and XAS. Reversible oxygen release and re-accommodation by the host structure accounts, at least in part, for the unusual high capacity. The Li2 MnO3 character of Li- and Mn-rich metal oxide structures is preserved during the initial cycles.